2005
DOI: 10.1021/ja0550071
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, Strontium, Barium, and Ytterbium Complexes with Cyclooctatetraenyl or Cyclononatetraenyl Ligands1

Abstract: Neutral triple-decker complexes of the heavy alkaline earth metals and ytterbium with tetraisopropylcyclopentadienide anions as terminal ligands and a cyclooctatetraene dianion as a middle deck have been synthesized from tetraisopropylcyclopentadienyl metal halide precursors and disodium cyclooctatetraenide. The pentaisopropylcyclopentadienyl analogue [{(C5iPr5)Yb}2(C8H8)] was prepared from ytterbium metal, cyclooctatetraene, and the free pentaisopropylcyclopentadienyl radical. X-ray crystal structure determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 83 publications
1
44
0
Order By: Relevance
“…The 13 C NMR chemical shift of δ =97.1 ppm is shifted upfield with respect to uncoordinated cot ( δ =132.7 ppm), approaching the shift found in K 2 ‐cot ( δ =89.9 ppm),22 consistent with the increased ring current of the planar aromatic form. The corresponding cot coupling constant 1 J C‐H of 157 Hz is similar to those observed for [(Cp i Pr4 M) 2 (μ 2 ‐cot)] (M=Ca, Sr, Ba: 157, 157, and 158 Hz, respectively)19 and uncoordinated cot (155 Hz), but larger than for K 2 ‐cot (143 Hz) 22. A single resonance is found in the 119 Sn{ 1 H} NMR spectrum at δ =−85 ppm, well upfield of the range generally observed for two‐coordinate stannylenes (e.g.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The 13 C NMR chemical shift of δ =97.1 ppm is shifted upfield with respect to uncoordinated cot ( δ =132.7 ppm), approaching the shift found in K 2 ‐cot ( δ =89.9 ppm),22 consistent with the increased ring current of the planar aromatic form. The corresponding cot coupling constant 1 J C‐H of 157 Hz is similar to those observed for [(Cp i Pr4 M) 2 (μ 2 ‐cot)] (M=Ca, Sr, Ba: 157, 157, and 158 Hz, respectively)19 and uncoordinated cot (155 Hz), but larger than for K 2 ‐cot (143 Hz) 22. A single resonance is found in the 119 Sn{ 1 H} NMR spectrum at δ =−85 ppm, well upfield of the range generally observed for two‐coordinate stannylenes (e.g.…”
supporting
confidence: 79%
“…We present here studies of the reaction of 1 with cyclic polyolefinic molecules, in particular cyclooctatetraene (cot), 1,5‐cyclooctadiene (cod), 1,4‐cyclohexadiene and cyclohexene, and show that the reaction with cot results in the complete cleavage of the SnSn bond to give a new inverse‐sandwich structure composed of mono aryl–stannyl units and a planar C 8 H 8 ring. These types of cot‐bridged molecules are known for f‐block1417 and s‐block elements,18, 19 whereas transition metal analogues isolated to date display olefinic or “semi‐aromatic” cot character 2023. The inverse sandwich coordination archetype is unknown for cot derivatives of the p‐block elements and no π‐coordinated cot 2− complex of a p‐block element has been characterized.…”
mentioning
confidence: 99%
“…1,3,5,7-Cyclooctantetraene (COT) has 8 π-electrons, but does not possess any aromaticity. Recent experimental studies revealed that COT 2− could form stable complicated complex with Ba 2+ and cyclopentadiene anion derivatives, and their structure has been resolved by X-ray crystallography [47] . By theoretical calculations, Gong et al [44] demonstrated that COT could accept two electrons from alkaline-earth metal during the complexation reaction, resulting in a planar 10-electron planar structure of COT 2− (Figure 4).…”
Section: Theoretical Studies On Cation-π Interactionsmentioning
confidence: 99%
“…Actually, there are known to be several complexes with similar structures. Walter et al synthesized a complex with cyclooctatetraene and Ca, which has the same partial structure with 8‐Ca except for the existence of Cp ligands . Note here that the Cp ligands lead to the oxidation of Ca atoms, resulting in Ca 2+ without radical electron.…”
Section: Introductionmentioning
confidence: 99%